Presence, mobility and bioavailability of toxic metal(oids) in soil, vegetation and water around a Pb-Sb recycling factory (Barcelona, Spain). (June 2018) - Mykolenko, S.; Liedienov, V.; Kharytonov, M.; Makieieva, N.; Kuliush, T.; Queralt, I.; Marguí, E.; Hidalgo, M.; Pardini, G.; Gispert, M.
Abstract: The work was conducted to establish contamination from improper disposal of hazardous wastes containing lead (Pb) and antimony (Sb) into nearby soils. Besides other elements in the affected area, the biological role of Sb, its behaviour in the pedosphere and uptake by plants and the food chain was considered. Wastes contained 139532 ± 9601 mg kg −1 (≈14%) Pb and 3645 ± 194 mg kg −1 (≈0.4%) Sb respectively and variability was extremely high at a decimetre scale. Dramatically high concentrations were also found for As, Cd, Cu, Mn, Ni, Sn and Zn. In adjacent natural soils metal(oid)s amounts decreased considerably (Pb 5034 ± 678 mg kg −1, Sb 112 mg kg −1 ) though largely exceeded the directives for a given soil use. Metal(oid)s potential mobility was assessed by using H2 O→KNO3 →EDTA sequential extractions, and EDTA extracts showed the highest concentration suggesting stable humus-metal complexes formation. Nevertheless, selected plants showed high absorption potential of the investigated elements. Pb and Sb values for Dittrichia viscosa grown in wastes was 899 ± 627 mg kg −1 and 37 ± 33 mg kg −1 respectively. The same plant showed 154 ± 99 mg kg −1 Pb and 8 ± 4 mg kg −1 Sb in natural soils. Helichrysum stoechas had 323 ± 305 mg kg −1 Pb, and 8 ± 3 mg kg −1 Sb. Vitis vinifera from alongside vineyards contained 129 ± 88 mg kg −1 Pb and 18 ± 9 mg kg −1 Sb, indicating ability for metal uptake and warning on metal diffusion through the food chain. The biological absorption coefficient (BAC) and the translocation factor (TF) assigned phytoextraction potential to Dittrichia viscosa and Foeniculum vulgare and phytostabilization potential to Helichrysum stoechas . Dissolved metal (oid)s in the analysed water strongly exceeded the current directive being a direct threat for livings. Data warned against the high contamination of the affected area in all its compartments. Even though native plants growing in metal-contaminated sites may have phytoremediation potential, high risk of metal diffusion may threat the whole ecosystem. Graphical abstract: Image 1 Highlights: High metal (oid)s concentrations warn on pollution hazard and pose environmental risk. Low theoretical toxic element mobility to biota may be underestimated. High concentration of metals and metalloids absorbed by selected plants. Helichrysum stoechas and Dittricia vioscosa phytoremediation efficiency proved. Foeniculum vulgare as new native plant for natural phytoremediation. Abstract : Toxic metal (oid)s persist for a long time threating ecosystems quality and human health, thus the identification of areas at risk, their extent and potential hazard through dispersal and bioavailability is of great relevance prior to establish remediation technologies.